The Bridge Project Improving Heart Failure Care in Skilled Nursing Facilities - Boxer, Rebecca S. (2011)
INTRODUCTION: Re-hospitalization rates and transitions of care for patients with heart failure (HF) continue to be of prominent importance for hospital systems around the United States. Skilled nursing facilities (SNF) are pivotal sites for transition especially for older adults. The purpose of this study was to evaluate in SNFs both the 1) current state of HF management (HF admissions, protocols and staff knowledge) and 2) the acceptability and effect of a HF staff educational program METHODS: Four SNFs participated in the project, two the first year and two the second year. SNFs were surveyed by discipline as to HF disease management techniques. Staff were evaluated on HF knowledge and confidence in pre and post HF disease management training. RESULTS: All-cause rehospitalization rates ranged from 18% to 43% in the 2 SNF evaluated. Overall, there was a lack of identification and tracking of HF patients in all the SNFs. There were no HF-specific disease management protocols at any SNF and staff had limited knowledge of HF care. Staff pre and post test scores indicated an improvement in both staff knowledge and confidence in HF management after receiving training. CONCLUSION: The lack of identification and tracking of patients with HF limits SNF ability to care for patients with HF. HF education for staff is likely important to effective HF management in the SNF.